Low-profile, wideband, wide-scanning tightly coupled dipole phased array antenna - Dang, Wen; Yong, Wai Yan; Glazunov, Andrés Alayón (Frontiers in Communications and Networks, 2025)
This paper presents a low-profile, tightly coupled dipole array (TCDA) antenna to achieve broad-angle scanning with excellent impedance matching over a wide bandwidth. The antenna element is innovatively designed using two planar shorted patches, forming a compact structure. A pair of parasitic strips is incorporated between adjacent antenna elements to ensure surface current uniformity across a wide frequency range. A high-index semi-arc metasurface (MS) is engineered as a wide-angle impedance matching (WAIM) layer to enhance the scanning performance in both E− and H-planes without compromising the low-profile form factor. Full-wave simulations demonstrate that the proposed antenna array supports a wide scanning range of up to ±60° in both E− and H-planes over an ultra-wide bandwidth of 12−30 GHz at VSWR≤2.5. A 5×5 array prototype was fabricated and experimentally tested to validate the design concept. The measurement results exhibit good agreement with simulations, confirming the efficacy and practicability of the proposed TCDA design. The proposed array achieves wideband impedance matching and wide-angle scanning capability within a compact, planar structure, making it highly suitable for mobile satellite communications and emerging 6G systems requiring agile beam steering.